DIVIDEND POLICY AS MEDIATION OF THE INFLUENCE OF MANAGEMENT OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON COMPANY’S FINANCIAL PERFORMANCE - Supriyono -; Dian Wismar’ein (Conference In Business, Accounting, And Management (CBAM), 2015)
The purposes of this research are: (1) to examine if management ownership influences significantly positive on dividend policy (2) to examine if institutional ownership influences significantly positive on dividend policy, and (3) to examine if dividend policy influences significantly positive on company’s financial performance. This is an explanatory research since it aims to explain the influence among variables after testing research hypotheses based on the underlying theory. The data of this research are financial reports of go public manufacture companies which have been audited at Indonesian Stock Exchange (IDX) from 2003 – 2012. This is a census research that is by using all population, 36 manufacture companies. Since this is a census research by using pooling data technique for 10 years so there were 360 observation data. This research used path analysis technique to test hypotheses. The research finding shows that management ownership doesn’t influence significantly positive on dividend policy, institutional ownership doesn’t influence significantly positive on dividend policy, dividend policy doesn’t influence significantly positive on company’s financial performance, Keywords : dividend policy, management ownership, institutional ownership, and company’s financial performance